Ranibizumab for exudative AMD in a clinical setting: differences between 2007 and 2010 - Cohen, Salomon Y.; Dubois, Lise; Ayrault, Sandrine; Dourmad, Pauline; Delahaye-Mazza, Corinne; Fajnkuchen, Franck; Nghiem-Buffet, Sylvia; Quentel, Gabriel; Tadayoni, Ramin (Graefe's archive for clinical and experimental ophthalmology, 2013)
Background/purpose Visual results of ranibizumab given pro re nata in clinical settings depend greatly from the achievement of the monthly follow-up. In 2007, a previous study performed in our tertiary care showed a mean visual gain of only + 0.7 ETDRS chart letters, probably because of insufficient number of follow-up visits and injections. We report a second retrospective study of patients whose eyes were treated in the same setting, and whose first injection was performed after April 1 2010. The aim was to check if the changes in the management of AMD patients between 2010 and 2007 achieved better visual results. Method One hundred and twenty-two patients (125 eyes) with exudative age-related macular degeneration (AMD) were included. Age, gender, side, type of CNV, VA measured on an ETDRS chart at baseline and at 52 ± 6 weeks, the number of IVT performed, and follow-up visits were recorded. The series was compared to our former series of the year 2007. Results are expressed as means ± standard deviation. Mann–Whitney’s non-parametric test was used to compare the statistical distribution of the parameters measured. Fisher’s exact test was used for 2 × 2 categorical variables, and the chi-square test for others. Results In the 2010 series, the mean visual gain was +6.0 ± 11.0 l (−35 to + 34). During this period, the eyes had 5.0 ± 1.8 IVT and 7.8 ± 1.4 follow-up visits. No correlation was found between the change in VA and gender, type of CNV, age, or the numbers of IVT and visits. There was a reverse correlation between baseline VA and VA changes ( r = −0.413, p < 0.0001): i.e., the higher the VA at presentation, the smaller the gain. Comparison between 2010 and 2007 showed that in 2010, patients were older (82.2 ± 7.0 vs 78.3 ± 7.0 y, p < 0.0001), had a better baseline VA (60.6 ± 12.7 vs 56.1 ± 14.6 l, p = 0.0191) and, despite the reverse correlation between change in VA and VA at presentation, visual results were better: +6.0 ± 11.0 vs +0.7 ± 11.99 l, p = 0.0003. In 2010, eyes received more injections: 5.0 ± 1.8 vs 3.8 ± 1.4 in 2007, p < 0.0001. However, the series did not differ for the number of visits, gender, side or type of CNV. Conclusions In 2010, monotherapy with ranibizumab for exudative AMD achieved better visual results than in 2007 in our clinical setting, despite the treatment of older patients with better baseline VA. This is probably due to the greater number of IVT performed. Alternate strategies, such as “inject and extend” or maintenance therapy, may also account for the better visual results.